Alice Paul and the fight for women's rights : from the vote to the equal rights amendment - Kops, Deborah (Calkins Creek, an imprint of Highlights, 2017)
Describes the life and accomplishments of the women's rights activist, from her youth to the passage of the Equal Rights Amendment.